The Factors Impact Information Technology Adoption Among Employees at Tax Authority of Yemen - Al-Douis, Gamal Abdulah (2010)
Information is powerful. This great statement led to do this research by seeing information technology power in developing several countries such as Malaysia. Due to the increased organizational dependence on information systems and technology, most of today's organizations and governments have plans to implement information technology in all of their job processing and communication tools. This study aims to describe the current state of information technology adoption among employees in Tax Authority of Yemen and to find the relationship with complexity, compatibility, and relative advantages. To deepen the analysis, reliability test has been done, then, study used liner regression to test the hypothesis. Moreover, descriptive statistics was computed to describe the current state of information technology adoption by using tables, charts and graphs to present the findings in an understandable manner. As a result of the study relative advantages has the highest relationship, then compatibility, and complexity. This research provided some recommendations through its results both can help the top management of tax authority of the Republic of Yemen push growing of information technology implementation.